Diagnostic value of dynamic-extended focused assessment with sonography for trauma in patients with multiple trauma - Xu, Yongsong; Wang, Runze; Zhu, Mengmeng; Li, Xuexue; Pan, Xiaodong; Ni, Tong; Zhou, Shusheng (Zhonghua wei zhong bing ji jiu yi xue, 2018)
To investigate the diagnostic value of dynamic-extended focused assessment with sonography for trauma (D-EFAST) in patients with multiple trauma in intensive care unit (ICU). A prospective clinical study was conducted. Eighty patients with multiple trauma admitted to ICU of Anhui Provincial Hospital from September 1st, 2014 to December 31st, 2016 were enrolled. Extended focused assessment with sonography for trauma (E-FAST) check was conducted at first, for those who had positive findings diagnosis was confirmed by immediately CT examination or surgical exploration. If it was negative, the patients received E-FAST every morning for 7 days (defined as D-EFAST), for those with positive findings, immediately CT or surgery was performed to clarify the diagnosis. The final clinical diagnosis was used as the "gold standard" to calculate the diagnostic accordance rate of EFAST and D-EFAST examination technique for pneumothorax, pleural effusion, spleen injury, kidney damage, liver damage, gastrointestinal injury, pe